Learning Models to Improve Basic Movement in Elementary School Physical Education Learning: Literature Review - Indra Presatria; Mashud Mashud (Sinar Sport Journal, 2026)
Fundamental movement skills are an essential foundation for the motor development of elementary school students; however, students' basic movement learning outcomes still need improvement through the implementation of appropriate learning models. This study aimed to identify learning models used to improve elementary school students' basic movement learning outcomes, analyze their effectiveness, and examine research trends in this area. This study employed a systematic literature review by searching articles indexed in the Google Scholar database published between 2016 and 2026. The processes of identification, screening, and article selection were conducted systematically based on predetermined inclusion and exclusion criteria. Out of 500 identified articles, 21 articles met the criteria and were included in the analysis. The findings revealed that game-based learning models, traditional games, tactical approaches, interactive multimedia, and motor activity-based learning effectively improved elementary school students' fundamental movement skills. In addition, these learning models were found to enhance students' learning motivation and participation in physical education classes. Therefore, active, innovative, and movement-based learning models can serve as effective alternatives for improving elementary school students' basic movement learning outcomes.